Status and Evolving Characteristics of Marine Spatial Resources in the Hangzhou Bay Area of Zhejiang Province, China - Peng Wang; Jingru Zhou; Kaixuan Zheng; Xia Lin; Mou Leong Tan; Jingchao Shi; Xingwen Lin; Xihe Yue; Xu Ma; Fei Zhang (Journal of Marine Science and Engineering)
The 20th Party Congress initiated efforts to strengthen maritime power and advance marine ecological civilization, which is essential for promoting sustainable development. To achieve this goal, this study combines field measurements, drone imagery, and high-resolution remote sensing data, using GIS technology to analyze changes in marine resources in Hangzhou Bay and assess marine area usage, intertidal zone area changes, and coastline erosion. The key findings show that the industrial sector accounts for the largest usage of marine area, with the industrial sea area growing by 110.3% from 2018 to 2020. The diversity index for marine area usage in Hangzhou Bay has remained stable, consistently at 0.6 and above over the past five years. The continental coastline of Hangzhou Bay has shown a decreasing trend in recent years from 2018 and 2021, with a total intertidal area of Hangzhou Bay decreased by 73.44 km2, where the overall shoal pattern in Hangzhou Bay remained relatively stable from 2008 to 2016. Erosion has been the predominant force, with maximum erosion surpassing 3 m and causing significant spatial changes. Between 2012 and 2016, the total erosion volume reached 192,473.74 × 106 m3, with an average annual erosion rate of 48,118.44 × 106 m3. This process has led to a gradual reduction in the size of affected areas over the period from 2001 to 2021. This research provides valuable insights for authorities to make informed decisions regarding the management of marine spatial resources in Hangzhou Bay.